Unlocking the potential of Chlorella sp. biomass: an effective adsorbent for heavy metals removal from wastewater - Tenza, Ntombiphumile Perceverence; Schmidt, Stefan; Mahlambi, Precious Nokwethemba (Frontiers in Environmental Chemistry, 2025)
Conventional wastewater treatment methods are often ineffective at fully removing heavy metals, leading to environmental and health risks. These methods are also chemically intensive and costly, emphasizing the need for sustainable alternatives. This study investigated Chlorella sp. biomass as a sustainable solution for removing heavy metals (copper, lead, and zinc) from wastewater in South Africa. The dried biomass was characterized using Energy Dispersive X-ray spectroscopy, Scanning Electron Microscopy, and Fourier-Transform Infrared Spectroscopy. Batch adsorption experiments were conducted under varying conditions: biomass dosage (5–100 mg), pH (3–11), contact time (15–115 minutes), and metal concentrations (0.25–16 mg/L) at 25°C. Adsorption isotherms, kinetics, and thermodynamic properties were also evaluated. The biomass composition revealed carbon, nitrogen, oxygen, phosphorus, and sulfur, with slightly higher nitrogen and sulfur levels than reported. Functional groups such as hydroxyl, carboxyl, carbonyl, amide, and ether were identified by FTIR. Optimal conditions for heavy metal removal were pH 7, 60 minutes of contact time, 12.5 mg biomass dosage, and 0.5 mg/L metal concentration. In wastewater samples, Chlorella sp. biomass achieved 100% removal of copper and zinc and 98% removal of lead. Adsorption followed the Langmuir isotherm for copper (R2 = 0.9888) and the Freundlich isotherm for lead (R2 = 0.976) and zinc (R2 = 0.968). Kinetic studies followed a pseudo-first-order model, and thermodynamic analysis indicated an endothermic and spontaneous adsorption process for copper and zinc, with lead showing complete removal at all temperatures. Chlorella sp. biomass demonstrated high efficiency and sustainability in removing heavy metals from wastewater, offering a promising alternative to conventional methods. Future research should focus on improving removal by combining Chlorella sp. biomass with other microorganisms and scaling up to pilot applications.